Alignment and Graphene-Assisted Decoration of Lyotropic Chromonic Liquid Crystals Containing DNA Origami Nanostructures - Martens, Kevin; Funck, Timon; Kempter, Susanne; Roller, Eva-Maria; Liedl, Tim; Blaschke, Benno M.; Knecht, Peter; Garrido, José Antonio; Zhang, Bingru; Kitzerow, Heinz-Siegfried (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Simulations of high harmonic generation from plasmonic nanoparticles in the terahertz region - Grynko, Yevgen; Zentgraf, Thomas; Meier, Torsten; Förstner, Jens (Applied Physics B)
Keywords: tet_topic_meta; tet_topic_shg

Quantum interference control of electrical currents in GaAs microstructures: physics and spectroscopic applications - Sternemann, E.; Jostmeier, T.; Ruppert, C.; Thunich, S.; Duc, H. T.; Podzimski, R.; Meier, Torsten; Betz, M. (Applied Physics B)

Indium oxide inverse opal films synthesized by structure replication method - Amrehn, Sabrina; Berghoff, Daniel; Nikitin, Andreas; Reichelt, Matthias; Wu, Xia; Meier, Torsten; Wagner, Thorsten (Photonics and Nanostructures - Fundamentals and Applications)
We present the synthesis of indium oxide (In2O3) inverse opal films with photonic stop bands in the visible range by a structure replication method. Artificial opal films made of poly(methyl methacrylate) (PMMA) spheres are utilized as template. The opal films are deposited via sedimentation facilitated by ultrasonication, and then impregnated by indium nitrate solution, which is thermally converted to In2O3 after drying. The quality of the resulting inverse opal film depends on many parameters; in this study the water content of the indium nitrate/PMMA composite after drying is investigated. Comparison of the reflectance spectra recorded by vis-spectroscopy with simulated data shows a good agreement between the peak position and calculated stop band positions for the inverse opals. This synthesis is less complex and highly efficient compared to most other techniques and is suitable for use in many applications.

Dynamics of dipoles and vortices in nonlinearly coupled three-dimensional field oscillators - Driben, R.; Konotop, V. V.; Malomed, B. A.; Meier, Torsten (Physical Review E)
The dynamics of a pair of harmonic oscillators represented by three-dimensional fields coupled with a repulsive cubic nonlinearity is investigated through direct simulations of the respective field equations and with the help of the finite-mode Galerkin approximation (GA), which represents the two interacting fields by a superposition of 3+3 harmonic-oscillator p-wave eigenfunctions with orbital and magnetic quantum numbers l=1 and m=1, 0, −1. The system can be implemented in binary Bose-Einstein condensates, demonstrating the potential of the atomic condensates to emulate various complex modes predicted by classical field theories. First, the GA very accurately predicts a broadly degenerate set of the system's ground states in the p-wave manifold, in the form of complexes built of a dipole coaxial with another dipole or vortex, as well as complexes built of mutually orthogonal dipoles. Next, pairs of noncoaxial vortices and/or dipoles, including pairs of mutually perpendicular vortices, develop remarkably stable dynamical regimes, which feature periodic exchange of the angular momentum and periodic switching between dipoles and vortices. For a moderately strong nonlinearity, simulations of the coupled-field equations agree very well with results produced by the GA, demonstrating that the dynamics is accurately spanned by the set of six modes limited to l=1.

Photocurrents in semiconductors and semiconductor quantum wells analyzed by k.p-based Bloch equations - Podzimski, Reinold; Duc, Huynh Thanh; Priyadarshi, Shekhar; Schmidt, Christian; Bieler, Mark; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XX)

Advanced optical manipulation of carrier spins in (In,Ga)As quantum dots - Varwig, S.; Evers, E.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Meier, Torsten; Zrenner, Artur; Bayer, M. (Applied Physics B)
Spins in semiconductor quantum dots have been considered as prospective quantum bit excitations. Their coupling to the crystal environment manifests itself in a limitation of the spin coherence times to the microsecond range, both for electron and hole spins. This rather short-lived coherence compared to atomic states asks for manipulations on timescales as short as possible. Due to the huge dipole moment for transitions between the valence and conduction band, pulsed laser systems offer the possibility to perform manipulations within picoseconds or even faster. Here, we report on results that show the potential of optical spin manipulations with currently available pulsed laser systems. Using picosecond laser pulses, we demonstrate optically induced spin rotations of electron and hole spins. We further realize the optical decoupling of the hole spins from the nuclear surrounding at the nanosecond timescales and demonstrate an all-optical spin tomography for interacting electron spin sub-ensembles.
Keywords: Spin Polarization; Pump Pulse; Trion; Spin Component; Coherence Time

Two-dimensional symbiotic solitons and vortices in binary condensates with attractive cross-species interaction - Ma, Xuekai; Driben, Rodislav; Malomed, Boris A.; Meier, Torsten; Schumacher, Stefan (Scientific Reports)

Ultrafast shift and rectification photocurrents in GaAs quantum wells: Excitation intensity dependence and the importance of band mixing - Duc, Huynh Thanh; Podzimski, Reinold; Priyadarshi, Shekhar; Bieler, Mark; Meier, Torsten (Physical Review B)
A microscopic approach that is based on the multisubband semiconductor Bloch equations formulated in the basis of a 14-band k⋅p model is employed to compute the temporal dynamics of photocurrents in GaAs quantum wells following excitation with femtosecond laser pulses. This approach provides a transparent description of the interband, intersubband, and intraband excitations, fully includes all resonant as well as off-resonant excitations, and treats the light-matter interaction nonperturbatively. For linearly polarized excitations, the photocurrents contain contributions from shift and rectification currents. We numerically compute and analyze these currents generated by excitation with femtosecond laser pulses for [110]- and [111]-oriented GaAs quantum wells. It is shown that the often employed perturbative χ(2) approach breaks down for peak fields larger than about 10 kV/cm, and that nonperturbative effects lead to a reduction of the peak values of the shift and rectification currents and to temporal oscillations that originate from Rabi flopping. In particular, we find a complex oscillatory photon energy dependence of the magnitudes of the shift and rectification currents. Our simulations demonstrate that this dependence is the result of mixing between the heavy- and light-hole valence bands. This is a surprising finding since the band mixing has an even larger influence on the strength of the photocurrents than the absorption coefficient. For [110]-oriented GaAs quantum wells, the calculated photon energy dependence is compared to experimental results, and good agreement is obtained. This validates our theoretical approach.

Precession and nutation dynamics of nonlinearly coupled non-coaxial three-dimensional matter wave vortices - Driben, R.; Konotop, V. V.; Meier, Torsten (Scientific Reports)
Nonlinearity is the driving force for numerous important effects in nature typically showing transitions between different regimes, regular, chaotic or catastrophic behavior. Localized nonlinear modes have been the focus of intense research in areas such as fluid and gas dynamics, photonics, atomic and solid state physics etc. Due to the richness of the behavior of nonlinear systems and due to the severe numerical demands of accurate three-dimensional (3D) numerical simulations presently only little knowledge is available on the dynamics of complex nonlinear modes in 3D. Here, we investigate the dynamics of 3D non-coaxial matter wave vortices that are trapped in a parabolic potential and interact via a repulsive nonlinearity. Our numerical simulations demonstrate the existence of an unexpected and fascinating nonlinear regime that starts immediately when the nonlinearity is switched-on and is characterized by a smooth dynamics representing torque-free precession with nutations. The reported motion is proven to be robust regarding various effects such as the number of particles, dissipation and trap deformations and thus should be observable in suitably designed experiments. Since our theoretical approach, i.e., coupled nonlinear Schrödinger equations, is quite generic, we expect that the obtained novel dynamical behavior should also exist in other nonlinear systems.

Ultrafast dynamical response of the lower exciton-polariton branch in CdZnTe - Lohrenz, J.; Melzer, S.; Ruppert, C.; Akimov, I. A.; Mariette, H.; Reichelt, Matthias; Trautmann, Alexander; Meier, Torsten; Betz, M. (Physical Review B)
We investigate the transient optical response in high-quality Cd0.88Zn0.12Te crystals in the regime of slow light propagation on the lower exciton-polariton branch. Femtosecond photoexcitation leads to very substantial transmission changes in a ∼10-meV broad spectral range within the transparency window of the unexcited semiconductor. These nonlinear optical signatures decay on picosecond time scales governed by carrier thermalization and recombination. The temporal and spectral dependence indicate the dynamical optical response as arising from excitation-induced dephasing and perturbed free induction decay. Model simulations for the optical response taking into account the actual exciton-polariton dispersion and excitation-induced dephasing of a nonlinearly driven two-level system support this interpretation.

Identification of ferroelectric domain structure sensitive phonon modes in potassium titanyl phosphate: A fundamental study - Rüsing, Michael; Eigner, Christof; Mackwitz, P.; Berth, Gerhard; Silberhorn, Christine; Zrenner, Artur (Journal of Applied Physics)
Confocal Raman spectroscopy is applied to identify ferroelectric domain structure sensitive phonon modes in potassium titanyl phosphate. Therefore, polarization-dependent measurements in various scattering configurations have been performed to characterize the fundamental Raman spectra of the material. The obtained spectra are discussed qualitatively based on an internal mode assignment. In the main part of this work, we have characterized z-cut periodically poled potassium titanyl phosphate in terms of polarity- and structure-sensitive phonon modes. Here, we find vibrations whose intensities are linked to the ferroelectric domain walls. We interpret this in terms of changes in the polarizability originating from strain induced by domain boundaries and the inner field distribution. Hence, a direct and 3D visualization of ferroelectric domain structures becomes possible in potassium titanyl phosphate.

Fabrication and characterization of two-dimensional cubic AlN photonic crystal membranes containing zincblende GaN quantum dots - Blumenthal, Sarah; Bürger, Matthias; Hildebrandt, Andre; Förstner, Jens; Weber, Nils; Meier, Cedrik; Reuter, Dirk; As, Donat J. (physica status solidi (c))
We successfully developed a process to fabricate freestanding cubic aluminium nitride (c-AlN) membranes containing cubic gallium nitride (c-GaN) quantum dots (QDs). The samples were grown by plasma assisted molecular beam epitaxy (MBE). To realize the photonic crystal (PhC) membrane we have chosen a triangular array of holes. The array was fabricated by electron beam lithography and several steps of reactive ion etching (RIE) with the help of a hard mask and an undercut of the active layer. The r/a- ratio of 0.35 was deter- mined by numerical simulations to obtain a preferably wide photonic band gap. Micro-photoluminescence (μ-PL) measurements of the photonic crystals, in particular of a H1 and a L3 cavity, and the emission of the QD ensemble were performed to characterize the samples. The PhCs show high quality factors of 4400 for the H1 cavity and about 5000/3000 for two different modes of the L3 cavity, respectively. The energy of the fundamental modes is in good agreement to the numerical simulations.
Keywords: tet_topic_phc; tet_topic_qd

Periodic domain inversion in x-cut single-crystal lithium niobate thin film - Mackwitz, P.; Rüsing, Michael; Berth, Gerhard; Widhalm, A.; Müller, K.; Zrenner, Artur (Applied Physics Letters)
We report the fabrication of periodically poled domain patterns in x-cut lithium niobate thin-film. Here, thin films on insulator have drawn particular attention due to their intrinsic waveguiding properties offering high mode confinement and smaller devices compared to in-diffused waveguides in bulk material. In contrast to z-cut thin film lithium niobate, the x-cut geometry does not require back electrodes for poling. Further, the x-cut geometry grants direct access to the largest nonlinear and electro-optical tensor element, which overall promises smaller devices. The domain inversion was realized via electric field poling utilizing deposited aluminum top electrodes on a stack of LN thin film/SiO2 layer/Bulk LN, which were patterned by optical lithography. The periodic domain inversion was verified by non-invasive confocal second harmonic microscopy. Our results show domain patterns in accordance to the electrode mask layout. The second harmonic signatures can be interpreted in terms of spatially, overlapping domain filaments which start their growth on the þz side.

Joint Raman spectroscopy and HRXRD investigation of cubic gallium nitride layers grown on 3C-SiC - Rüsing, Michael; Wecker, T.; Berth, Gerhard; As, Donat Josef; Zrenner, Artur (physica status solidi (b))
Cubic gallium nitride (GaN) films are analyzed with highresolution X-ray diffraction (HRXRD) and Raman spectroscopy. Several cubic GaN layers were grown on 3C-SiC (001) substrate by radio-frequency plasma-assisted molecular beam epitaxy. The layer thickness of the cubic GaN was varied between 75 and 505 nm. The HRXRD analysis reveals a reduction of the full-width at half-maximum (FWHM) of omega scans for growing layer thicknesses, which is caused by a partial compensation of defects. The Raman characterization confirms well-formed c-GaN layers. A more detailed examination of the longitudinal optical mode hints at a correlation of the FWHM of the Raman mode with the dislocation density, which shows the possibility to determine dislocation densities by Ramanspectroscopy on a micrometer scale, which is not possible by HRXRD. Furthermore, this Raman analysis shows that normalized Raman spectra present an alternative way to determine layer thicknesses of thin GaN films.
Keywords: cubic gallium nitride; dislocation density; HRXRD; Raman spectroscopy

Vibrational properties of LiNb1−xTaxO3 mixed crystals - Rüsing, Michael; Sanna, Simone; Neufeld, Sergej; Berth, Gerhard; Schmidt, Wolf Gero; Zrenner, Artur; Yu, H.; Wang, Y.; Zhang, H. (Physical Review B)
Congruent lithium niobate and lithium tantalate mixed crystals have been grown over the complete compositional range with the Czochralski method. The structural and vibrational properties of the mixed crystals are studied extensively by x-ray diffraction measurements, Raman spectroscopy, and density functional theory. The measured lattice parameters and vibrational frequencies are in good agreement with our theoretical predictions. The observed dependence of the Raman frequencies on the crystal composition is discussed on the basis of the calculated phonon displacement patterns. The phononic contribution to the static dielectric tensor is calculated by means of the generalized Lyddane-Sachs-Teller relation. Due to the pronounced dependence of the optical response on the Ta concentration, lithium niobate tantalate mixed crystals represent a perfect model system to study the properties of uniaxial mixed ferroelectric materials for application in integrated optics.

Spatially indirect transitions in electric field tunable quantum dot diodes - Rai, Ashish K.; Gordon, Simon; Ludwig, Arne; Wieck, Andreas D.; Zrenner, Artur; Reuter, Dirk (physica status solidi (b))

Ultrafast carrier dynamics and resonant inter-miniband nonlinearity of a cubic GaN/AlN superlattice - Jostmeier, Thorben; Wecker, Tobias; Reuter, Dirk; As, Donat Josef; Betz, Markus (Applied Physics Letters)

Nuclear spin polarization in the electron spin-flip Raman scattering of singly charged (In,Ga)As/GaAs quantum dots - Debus, J.; Kudlacik, D.; Sapega, V. F.; Dunker, D.; Bohn, P.; Paßmann, F.; Braukmann, D.; Rautert, J.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Transform-limited single photons from a single quantum dot - Kuhlmann, Andreas V.; Prechtel, Jonathan H.; Houel, Julien; Ludwig, Arne; Reuter, Dirk; Wieck, Andreas D.; Warburton, Richard J. (Nature Communications)